Utilising CFD Analysis for the Purpose of Designing and Analysing the Airflow of a Hybrid Racing Car (International Journal of Food and Nutritional Sciences, 2021)
Hybrid electric vehicles also have several conventional automobile features. The drive system gets its juice from a gas or electric motor and an internal combustion engine. There is still the issue of waste emission due to the inclusion of internal combustion engines, and hybrid electric vehicles' structure and control process are both challengingFurthermore, we opened and closed a variety of outlets and opening and closing a variety of cooling air ducts to see how the design parameters would change. the first study found that airflow through the wheelhouses increases drag. In the second experiment, researchers used input ducts to regulate airflow from the grilles into the cooling system. A thermally-velocity-propelled unmanned land platform was investigated as a feasibility study. Component sizes and selections were made based on the desired drive parameters.In this project to design of this project was completed using NX 12.0 and Crash analysis will be performed in Ansys workbench software by Explicit Dynamic module by using different materials (Al 2024, Carbon steel) for car body and Velocity 120 km/h (-33340 mm/sec) with the CFD was done by compressed Air developing a new vehicle operating mode and reselecting its components.